Systematization of the experience of a collective vocational guidance session through the support of ChatGPT with eleventh-year students of the Colegio Científico Costarricense, Puntarenas Campus - Pablo Armando Sibaja-Mojica (Revista Costarricense de Orientación, 2025)
Objective: To systematize the experience of a collective vocational guidance session, supported by the use of ChatGPT, to clear up vocational doubts at the Colegio Científico de Puntarenas, to analyze its uses in the reflection and vocational decision-making of students and to extract learning, good practices and recommendations for future implementations in vocational guidance processes.